Vagus nerve stimulation: a physical therapy with promising potential for central nervous system disorders - Wang, Chaoran; Wu, Bangqi; Lin, Ruolan; Cheng, Yupei; Huang, Jingjie; Chen, Yuyan; Bai, Jing (Frontiers in Neurology, 2024)
The diseases of the central nervous system (CNS) often cause irreversible damage to the human body and have a poor prognosis, posing a significant threat to human health. They have brought enormous burdens to society and healthcare systems. However, due to the complexity of their causes and mechanisms, effective treatment methods are still lacking. Vagus nerve stimulation (VNS), as a physical therapy, has been utilized in the treatment of various diseases. VNS has shown promising outcomes in some CNS diseases and has been approved by the Food and Drug Administration (FDA) in the United States for epilepsy and depression. Moreover, it has demonstrated significant potential in the treatment of stroke, consciousness disorders, and Alzheimer’s disease. Nevertheless, the exact efficacy of VNS, its beneficiaries, and its mechanisms of action remain unclear. This article discusses the current clinical evidence supporting the efficacy of VNS in CNS diseases, providing updates on the progress, potential, and potential mechanisms of action of VNS in producing effects on CNS diseases.